Mental health in elite-level coaches: prevalence rates and associated impact of coach stressors and psychological resilience - Kegelaers, J.; Wylleman, P.; van Bree, I. N.; Wessels, F.; Oudejans, R. R. (International Sport Coaching Journal, 2021)
Coaching in elite sports can be a highly volatile and stressful profession. Nevertheless, limited knowledge is available on how coach stressors impact elite-level coaches` mental health. The present study therefore aimed to assess the self-perceived impact of coach stressors on coaches` mental health, in terms of psychological and social well-being, as well as the prevalence of symptoms of a number of common mental disorders. Furthermore, the role of resilience was examined as a potential protective resource against mental health issues in coaches. Data were collected cross-sectionally, using an online survey with 119 elite-level coaches from the Netherlands and Belgium. Results showed that, although coach stressors were commonly experienced, the self-perceived impact on mental health was low to moderate. Nevertheless, symptoms of common mental disorders were prevalent within the coaches, ranging from 39% for depression/anxiety to 19% for distress and adverse alcohol use. Furthermore, organizational stressors were found to be a positive predictor for symptoms of depression/anxiety, whereas resilience was a negative predictor. The results highlight the need for more research and attention to the mental health of coaches in elite sports.